Gastritis – facts and doubts - Muszyński, Jacek; Ziółkowski, Bartłomiej; Kotarski, Paweł; Niegowski, Adam; Górnicka, Barbara; Bogdańska, Magdalena; Ehrmann-Jóśko, Agnieszka; Zemlak, Magdalena; Młynarczyk-Bonikowska, Beata; Siemińska, Jolanta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Many clinicians consider chronic gastritis to be equivalent to Helicobacter pylori infection. However, it is known that there are numerous other causes of the condition. Aim : Determination of the incidence of gastritis in patients with dyspepsia referred for diagnostic endoscopy of the upper part of the digestive tract, identification of the parts of the stomach most frequently affected by the inflammation, as well as the impact of an insufficient number of collected samples on the correct diagnosis. Material and methods : Upper gastrointestinal endoscopy due to dyspepsia was performed in 110 patients. In the course of gastroscopy two biopsy specimens were collected for histopathological examination and towards H. pylori infection from the lesser and greater curvature in the antrum 3 cm from the pyloric sphincter, in the body – 4 cm proximally to the stomach angular incisure on the lesser curvature, and in the middle of the greater curvature, as well as in the subcardiac region on the side of the lesser and greater curvature. Results : In patients with dyspepsia H. pylori -negative chronic gastritis is more common than gastritis with accompanying H. pylori infection. Collection of too small a number of biopsy specimens results in failure to detect inflammatory changes and/or H. pylori infection, which may be limited to one part of the stomach. Biopsy specimens of gastric mucosa should be collected in compliance with the assumptions of the Sydney System. Helicobacter pylori infection in people with dyspepsia is now being reported more rarely than in the past (36%). Conclusions : In patients with dyspepsia chronic H. pylori -negative gastritis is more common than gastritis with an accompanying H. pylori infection. Helicobacter pylori infection is not always equivalent to the presence of chronic gastritis.